2019
DOI: 10.1108/bepam-02-2018-0049
|View full text |Cite
|
Sign up to set email alerts
|

Socially responsible procurement

Abstract: Purpose Socially responsible procurement (SRP) utilises government expenditure on construction procurement as a means of generating social value from construction activities. The paper proposes that SRP is a type of innovation delivering social value in the form of employment opportunities to local communities. The purpose of this paper is to investigate the use of SRP in Northern Ireland procurement and align the findings with existing literature. Design/methodology/approach A three-stage approach was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 71 publications
2
32
0
Order By: Relevance
“…These newer legislative acts and policies have spurred both public and private organizations to engage in social procurement [3,7,24,25], and in fact, social criteria relating to employment of vulnerable groups are today the second most used type of social criteria in public procurement in the construction sector [26]. In North Ireland and Scotland, new work roles which exclusively deal with social procurement are increasingly common, and in many ways, the work with social procurement has become business as usual [17,25]. This development, with the creation of new roles, is also seen in Sweden [19].…”
Section: Social Procurementmentioning
confidence: 99%
See 4 more Smart Citations
“…These newer legislative acts and policies have spurred both public and private organizations to engage in social procurement [3,7,24,25], and in fact, social criteria relating to employment of vulnerable groups are today the second most used type of social criteria in public procurement in the construction sector [26]. In North Ireland and Scotland, new work roles which exclusively deal with social procurement are increasingly common, and in many ways, the work with social procurement has become business as usual [17,25]. This development, with the creation of new roles, is also seen in Sweden [19].…”
Section: Social Procurementmentioning
confidence: 99%
“…Previous studies have investigated common perceptions and experiences of social procurement in the construction sector. Many actors within the sector are in favour of social procurement, and studies have found that it is a useful tool to deepen the collaboration throughout the supply chain, to enable knowledge sharing, to fulfil client demands, to build competences, and to create employment [1,16,17,25]. Furthermore, social procurement is found to have benefits such as improved work environment, less employee turnover, lower absenteeism and improved productivity [27].…”
Section: Social Procurementmentioning
confidence: 99%
See 3 more Smart Citations